UPAYA MENINGKATKAN HASIL BELAJAR SISWA MATEMATIKA MELALUI PENERAPAN METODE BELAJAR AKTIF MODEL MENINJAU KEMBALI KESULITAN DI KELAS II SDN 009 TANJUNG PALAS - Jus Sulastri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This study aimed to describe the results of learning through the use of media folders. The subjects of the research were grade II students at SDN 009 Tanjung Palas. Improved learning outcomes were assessed in terms of four categories: absorption, the effectiveness of learning, mastery learning completeness (both individually and classically), and the accuracy of learning results. The instruments used for data collection were oral tests and written tests in the form of worksheets, administered after the learning process. Results showed that the absorption of learning outcomes averaged 83%, which is considered very good. Learning effectiveness was categorized as very effective, with an average of 70. The completeness of student learning outcomes presented was 100%. In addition, there was an increase in student thoroughness in each cycle: the first cycle (58.82%), the second cycle (70.59%), and the third cycle (88.24%). Based on these results, it can be concluded that the use of media folders can improve students' mathematics learning outcomes.